The Development in Teaching Materials of Introduction to Business Using Business Planning : The Study to the Students at University of Muhammadiyah Sumatera Utara - Jasman Saripuddin Hsb, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The Development in Teaching Materials of Introduction to Business Using Business Planning : The Study to the Students at University of Muhammadiyah Sumatera Utara